Globally Securing Food in an Insecure World – Opportunities and Challenges (Alternate Horizons, 2021)
This paper looks into the necessity of a global governance system for food security from a "humane" side, with a focus on countries and MNCs. It also explores potential mechanisms to drive MNCs involvement in the global governance of food security into a more inclusive path. Furthermore, the paper explores a more sustainable side to globally governing food security.  All in all, this paper calls for the reshaping of a global governance system that better matches the root causes of food insecurity, rather than tries to solve hunger with food aid and provision. The solution starts with asking the right questions. The global governance system should adopt a sole human rights framework while addressing food insecurity. It should acknowledge that questions such as “for whose benefit?” is just as important as “how to produce more?”. Although effective, International Governmental Organizations should further consider how global rules affect different people, who will bear the risks, who will get the benefits from changes, who remain disempowered, and whose ability to control is neglected or enhanced. Global food policy should not just be feeding people, but rather feeding them equitably, appropriately, and sustainably. This brings about a new global food regime that’s integrative of the human right to food.
Keywords: Food Security; Right to food; Global Governance